Political-Religious Violence in Pakistan and its Factors: Security Measures to Denounce the Violence (Al-Qamar, 2019)
Political scientists and Islamic philosophers have long been discussing the different phenomena of violence. This article analyzes external and internal factor of violence in Pakistan, interpreting the religious and political dimension of the violence. The presence of external and more specifically internal factors are the real threats for the security of the country. Building from theoretical approaches, I fielded two dimensions of the political-religious violence, violence inside the country and outside the country. It is found out, on the one hand, that the both dimensions can be met with the profound enforcement of the law. On the other hand, both dimensions of the violence can be the big contributory factors of violence due to the poor promulgation of the law. Unjust political-religious dispensation inside the country rise the frustration, and outside support make it fertile and leads it towards violence. It is proposed that on equity bases, political-religious deprivation and absolute deprivation of the minority elite class can be disposed of. I also come up with balanced educational system, which should be the blend of traditionalism and modernism for the fulfilment of our spiritual dimension and for the greater understanding of our political-religious outlook.
Keywords: External and Internal; Contributory Factors; Vocational; Precipitants Links